A Blueprint for Productive Maintenance of Certification, But Is the American Board of Internal Medicine up to the Challenge?. Issue 12 (December 2020) - Alyesh, Daniel; Gambhir, Alok; Waase, Marc; Remo, Benjamin; Singh, Abhijeet; Green, Jacqueline; Kittleson, Michelle; Estes, N.A. Mark; Heist, E. Kevin
Abstract : The future of the American Board of Internal Medicine Maintenance of Certification (MOC) program is at a crossroads. The current MOC program lacks a clear visible mission, adds to modern health care's onerous bureaucracy, and thus pulls physicians from the most important humanistic aspects of their profession. The aim of the MOC program should be to promote the best patient care by ensuring certified physicians maintain core skills through continuous education and evaluation. The program should focus on education and be designed with the rigorous obligations of practicing physicians in mind. Moving forward, the American Board of Internal Medicine should cocreate MOC with the physician community and apply innovative adult education techniques. Over time, data-driven methods and member feedback should be used to provide continuous program improvement. This review describes the origins of the current state of MOC, explores its evidence base, provides examples of model programs for the maintenance of complex professional skills, and outlines guiding principles for the future of MOC.